2022
DOI: 10.1097/jcma.0000000000000723
|View full text |Cite
|
Sign up to set email alerts
|

Serum level and clinical significance of vitamin E in pregnant women with allergic rhinitis

Abstract: Background: Allergic rhinitis is a frequent disorder during pregnancy, while in children it is triggered by significantly lower serum vitamin E level. This research aimed to investigate whether serum vitamin E level exhibited clinical significance in pregnant women with allergic rhinitis. Methods: In this study, 37 pregnant women with allergic rhinitis and 35 healthy pregnant women were recruited. Allergic rhinitis severity was analyzed by the Total Nasal Symptom Score (TNSS) questionnaire. Blood samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 33 publications
(42 reference statements)
2
6
0
Order By: Relevance
“…15 That is the basic rationale of Drs Wu and Wang's aims to investigate whether the serum level of vitamin E exhibited clinical significance in pregnant women with allergic rhinitis. 10 As predicted, the authors found low serum level of vitamin E, as well as high serum level of IL-4, IL-13, and IgE in pregnant women with allergic rhinitis compared to those without. 10 However, it is still uncertain whether the aforementioned findings are a cause or only an end product.…”
supporting
confidence: 56%
See 3 more Smart Citations
“…15 That is the basic rationale of Drs Wu and Wang's aims to investigate whether the serum level of vitamin E exhibited clinical significance in pregnant women with allergic rhinitis. 10 As predicted, the authors found low serum level of vitamin E, as well as high serum level of IL-4, IL-13, and IgE in pregnant women with allergic rhinitis compared to those without. 10 However, it is still uncertain whether the aforementioned findings are a cause or only an end product.…”
supporting
confidence: 56%
“…Therefore, recent studies have focused on the direct measurement of these essential trace elements in pregnant women to evaluate their roles on women's health or fetal well-being and subsequent lifelong of the fetuses. 1,[10][11][12] In the coming issue of the Journal of the Chinese Medical Association, Drs Wu and Wang attempted to investigate the relationship between the maternal serum level of vitamin E and the occurrence of pregnant women with allergic rhinitits. 10 This retrospective case-controlled study enrolled 37 pregnant women with allergic rhinitis and 35 healthy women as controls, and the authors found that the serum level of vitamin E in pregnant women with allergic rhinitis was statistically significantly lower than that in pregnant women without, and additionally, the serum level of vitamin E was negatively correlated with the total nasal symptom score, reaching the conclusion that the decreased vitamin E may be correlated with the pathogenesis of allergic rhinitis in pregnant women.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…When the literature on the subject is examined, it is seen that the studies are generally related to pregnancy (Bostan & Kabukcuoglu, 2022;Castillo et al, 2022;Shimpuku et al, 2022), prenatal care (Das et al, 2022;Iwanowicz-Palus et al, 2022;Zbiri et al, 2021), depression (Shimpuku et al, 2022;Wu & Wang, 2022;Zhang et al, 2021), social support (McCormack et al, 2021Rayburn & Coatsworth, 2021), self-sufficiency (Bostan & Kabukcuoglu, 2022;Diotaiuti et al, 2022;Eidouzaei et al, 2022), fear of childbirth (Buran & Aksu, 2022;Eidouzaei et al, 2022;Gökçe İşbir et al, 2022), anxiety (Diotaiuti et al, 2022;Gargari et al, 2021;Iwanowicz-Palus et al, 2022), obesity (Hurst et al, 2021;Ortiz-Felix et al, 2021), breastfeeding (Bookhart et al, 2021;Oggero & Wardell, 2022;Taha et al, 2022), parenting (Abbass-Dick et al, 2017, postpartum care (Gagnon & Sandall, 2007;Hunter et al, 2009), quality improvement (Hurst et al, 2021;Louis-Jacques et al, 2020;Takako, 2020).…”
Section: Introductionmentioning
confidence: 99%